A new species of the genus Cylindratus Meng, Qin et Wang, 2020 from northern Vietnam, with first description of 5th instar larva and a key to Vietnamese Caliscelini (Hemiptera: Fulgoromorpha: Caliscelidae) - Gnezdilov, Vladimir M. (Zootaxa, 2021)
Cylindratus fansipan sp. nov. is described from Lao Cai Province of Northern Vietnam. It is the first record of the genus Cylindratus Meng, Qin et Wang, 2020 from Vietnam and the fourth genus of the subfamily Caliscelinae known from the country. A 5th instar larva of the genus Cylindratus is described and illustrated for the first time. A key to the Vietnamese Caliscelini is given.